A Universal Calculation Method for Jacobian Matrix of Parallel Mechanism - Zhang Shuangshuang; Yang Hongtao (Jixie chuandong)
The Jacobian matrix is a key concept in mechanisms and profoundly reflect the nature of the mechanism,which provides us not only a kinematics mapping relations,it also sets a basis for mechanism analysis and synthesis in the future.A universal calculation method for Jacobian matrix of parallel mechanism is presented based on screw theory.Due to its style of construction,tedious steps in normal calculation method,including observation and derivation are nicely avoided,which makes this new method much more simplified.Meanwhile,since its modularization in style,this method also provides its advantages in computer aided programming.A limited-DOF parallel manipulator 3-RPS is used as an example to testify the superiority of this method,which also set a good foundation for further performance analysis and design.